Ketidakadilan Gender Dalam Kehidupan Perempuan Tionghoa di Kota Medan - Rudiansyah . (JURNAL RUPA, 2017)
Research of gender study Tionghoa in Medan city commenced from basic question whether or not the life of Tionghoa society in Medan city in all aspects (social, culture, economy and politic) are based on impartial gender principle. Qualitative, quantitative, observation, indepth interview, questionare methods and library research are applied to study the above case. The result shows that the live Tionghoa society in Medan city is still influenced by traditional values, culture and life orientation that lead to gender inequality. These values appear from patrilineal kinship system: women social status with man sub-ordinate, women activities are more in domestic structure and their productive activities are limited to home anvironment (stall, shop, service, home industry).